Technological development in telemedicine: bibliometric analysis, research gaps, and literature trends - Erick de Freitas Moura; Ieda Kanashiro Makiya; Maurilio Barbosa de Oliveira da Silva (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2024)
The aim of this article was to analyze the literature on technological development in telemedicine through bibliometrics, by identifying the state of the art, research gaps, and trends in the literature. The analysis covers a total of 67 articles related to the field of study, published between 2010-2020 in the Springer Link, Science Direct, Wiley Online Library, Web of Science, and Scopus databases. The data was processed using the software StArt, Excel, IBM SPSS Statistics, and Iramuteq. The results presented bibliometric analysis of the articles, classified into the areas of Management (52.2%), IT (25.4%), and Medicine (22.4%), along with a Table of 34 suggestions for future research. Literature trends encompassed six study clusters (health, study, service, technology, patient, and telemedicine), which further subdivided into nine research themes (digital platform, telemedicine service management, telemedicine service operation, end-user perception, business opportunities, healthcare professional perception, covid-19, regulation, and robotics). An observed outcome was a significant increase in the number of publications in the area due to covid-19.